2019
DOI: 10.2147/opth.s199713
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optical coherence tomography patterns of diabetic macular edema in a Saudi population</p>

Abstract: Purpose: The study aims to describe the patterns of diabetic macular edema (DME) and their association with visual acuity using optical coherence tomography (OCT). Patients and methods: This is a retrospective observational study with chart review of patients with DME including both type 1 and 2 diabetics seen between January 2015 and January 2016. Main Outcome Measures: Type of diabetes, diabetes duration, best-corrected visual acuity, DME pattern, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“… 11 In the present study, cystoid pattern was the most common morphological pattern, and CME was almost equally present in all the study groups, similar to Acan et al 12 DRT is the most common pattern according to many studies. 11 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“… 11 In the present study, cystoid pattern was the most common morphological pattern, and CME was almost equally present in all the study groups, similar to Acan et al 12 DRT is the most common pattern according to many studies. 11 …”
Section: Discussionsupporting
confidence: 89%
“…In contrast, a study done by Yassin et al concluded that CST had a positive correlation with the severity of the disease when different stages of DR were taken into consideration, with high-risk PDR (P=0.050) and severe NPDR (P=0.021) being statistically significant. 11 In the present study, cystoid pattern was the most common morphological pattern, and CME was almost equally present in all the study groups, similar to Acan et al 12 DRT is the most common pattern according to many studies. 11 Yassin et al also concluded that DRT is associated with significantly good visual acuity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The tomograph gives the opportunity to study in detail the structure of the optic nerve head at the early stages of glaucoma. The earliest changes in the optic nerve head are not detected ophthalmoscopically [18][19][20][21].…”
Section: Methods For Diagnosing Two Diseasesmentioning
confidence: 99%